Perjumpaan school: a new model of character learning in plural community - Abdul Quddus (ATTARBIYAH: Journal of Islamic Culture and Education, 2020)
Family, education school and community are strategic educational institutions in shaping the character of the nation that upholds integrity, honesty and commitment, but the fact is that these various institutions have not yet fully embodied the characters they aspire. Many character problems and abnormal social relations are experienced by learners in Indonesian educational institutions. Various models of character internalization emerged and developed to respond to this fact, including the Integrated Islamic School (SIT) education model, Living Values Education (LVE), The ESQ Way 165 and the Perjumpaan School Community. This article aims to analyze the character learning model developed by Perjumpaan School. This study uses qualitative research with descriptive analysis as a model for data analysis. This study found that Perjumpaan School has developed a new model in character learning. Perjumpaan School emphasized mental state management and languaging. Mental state is related to positive feelings or emotions while languaging is the use of norms inherent in language action. Positivity mental state and languaging in every encounter are efforts to normalize social relations that are open, tolerant and mutually acceptable to plural society.